Transcapsular scleral fixation of the standard capsular tension ring and in-the-bag intraocular lens implantation for severely subluxated lenses - Hong-Zhe Li; Fu-Man Yang; Ze-Hui Zhu; Yin-Ying Zhao; Ping-Jun Chang; Yun-E Zhao (International Journal of Ophthalmology, 2024)
AIM: To present a technique of transcapsular scleral fixation of the standard capsular tension ring (CTR) through equatorial capsulotomy and in-the-bag intraocular lens (IOL) implantation in subluxated lenses. METHODS: This retrospective consecutive case series included patients with subluxated lenses by more than 180 degrees who underwent lens extraction, transcapsular scleral fixation of the standard CTR through equatorial capsulotomy, in-the-bag IOL implantation and with at least 6mo follow-up. Preoperative and postoperative best corrected visual acuity (BCVA), intraocular pressure (IOP), complications, and postoperative IOL tilt and decentration were recorded. RESULTS: Nine eyes of 7 patients with a mean follow-up of 11.0±3.7mo were included in this study. The BCVA was significantly improved from 0.64±0.22 logMAR preoperatively to 0.21±0.19 logMAR postoperatively (P<0.001). The IOP was within the normal range postoperatively. The mean tilt of the IOL was 4.30°±2.31° (range, 1.0° to 8.9°) and the mean decentration of the IOL was 0.37±0.12 mm (range, 0.14 to 0.50 mm). No visually threatened intraoperative and postoperative complications were detected during the follow-up period. CONCLUSION: This is a safe and effective surgical technique for managing patients with severely subluxated lenses. It has achieved favorable outcomes with fewer surgical manipulations and less need for advanced capsular support devices.